Insights Into Pulp Biomineralization in Human Teeth - He, Rui; Chou, Conrad; Chen, Ling; Stoller, Marshall; Kang, Misun; Ho, Sunita P. (Frontiers in Dental Medicine, 2022)
INTRODUCTION: Mineralized pulp (MP) compromises tooth function and its causation is largely unknown. The hypothesis of this study is that pulp mineralization is associated with pupal tis-sue adaptation and increased mineral densities and decreased permeabilities of tubular dentin and cementum. Methods will include correlative spatial mapping of physicochemical and biochemical characteristics of pulp, and contextualize these properties within the dentin pulp complex to reveal the inherent vunerabilities of pulp. METHODS: Specimens (N = 25) were scanned using micro X-ray computed tomography to visualize MP and measure mineral density (MD). Elemental spatial maps of MP were acquired using synchrotron X-ray fluorescence microprobe (µXRF) and energy dispersive X-ray spectroscopy (EDX). Extracted pulp tissue were sectioned for immunolabelling and the localized labels were imaged using a light microscope. Microscale morphologies and nanoscale ultrastructures of the specimens were imaged using scanning electron (SEM) and scanning transmission electron (STEM) microscopy techniques. RESULTS: Heterogeneous distribution of MD with a wide range from 200 to 2200 mg/cc, and an average MD of 892 (±407) mg/cc were observed. Highly mineralized pulp was observed with increased number of occluded tubules, decreased connectivity in lateral channels, and reduced pore diameter in cementum. H&E, trichrome, and von Kossa staining showed lower cell and vessel densities in MP. The biomolecules osteopontin, osteocalcin, osterix, and bone sialoprotein were immunolocalized about PGP 9.5 positive neurovascular bundles in MP. SEM and STEM revealed a wide range of nano/micro particulates in dentin tubules and spherulitic mineral aggregates in the collagen matrix with intrafibrillar mineral surrounding neurovascular bundles. EDX and µXRF showed elevated counts of Ca, P, Mg, and Zn inside pulp and at the dentin-pulp interface. CONCLUSION: Colocalization of physical and chemical, and biomolecular compositions in MP suggest primary biomineralization pathways in the pulp and dentin at a tissue level, and secondary aggregate pathways involving altered fluid dynamics at an organ level. Elevated counts of Zn preceding the mineralizing front in MP indicated a role of Zn in pulp biomineralization. These observations underpin the inherent responsiveness of the neurovascular DPC and help elucidate the clinical subtleties related to pulpitis, pulp obliteration, dentin-bridge, and pulp stone formation.